Points of view : stories of psychopathology - Mitchell, James E. (James Edward), 1947- (Brunner-Routledge, 2001)
"This text will be of value and interest to descriptive psychopathology students, psychiatric residents, medical students, graduate students in psychology and psychiatry, students in various related mental health fields, including psychiatric nursing, social work, and counseling, and all preparing for a career in the mental health profession."--Jacket